FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENTINGNYA PRESTASI KERJA KARYAWAN SUATU TINJAUAN TEORITIS - Nasriah Akil (AkMen JURNAL ILMIAH, 2014)
Human Resources Company requires productive. Human Resources productive not only carry out work based tasks that have been assigned to him, but rather seeks to improve job performance or float. In principle, Human Resources is a very important factor, especially for an organization or business entity, whether engaged in the production of goods and services in the field of services (service). Human resource factors should receive top priority in its management so that organizations can achieve the goals that have been set previously.